Planeamento fiscal agressivo: delimitação concetual e perceção de utilização e consequências - Ferreira, Miguel Botelho Cardoso Rebelo (2021)
In an increasingly global market where the free movement of capital and headquarters is a reality, companies see the reduction of their tax burden as a competitive advantage and seek ways to obtain it. States, in return, are increasingly aware of this reality, but do not always choose restrictive measures and greater control over these matters. They react by trying to create an appealing tax environment, in which the most aggressive actions are rightful and legal, encouraging the circulation of high capitals and having a low percentage of withholding tax. Thus, the states themselves become more attractive to investment, trying to create innovation, employment and boost their economies. This reality makes the role of the entities responsible for tax control increasingly complex, with a greater focus on areas such as combating tax heavens and tax fraud. In the scope of our dissertation, the object of study will be, in the first place, the various forms of minimizing the tax burden and the exploration of the uncertainty of concepts. In a second chapter we will attempt to define the concept of Aggressive Tax Planning and list some of the strategies and mechanisms used to combat this practice internationally and nationally. Finally, we will present a survey with the objective of gauging the perception of the use of aggressive tax planning by Portuguese companies.